Time-Dependent Analysis of Catalytic Biomass Pyrolysis in a Continuous Drop Tube Reactor: Evaluating HZSM-5 Stability and Product Evolution - Chetna Mohabeer; Zineb Boutamine; Lokmane Abdelouahed; Antoinette Maarawi; Bechara Taouk (Biomass)
This study investigates a continuous deoxygenation of bio-oil vapor in a catalytic fixed-bed reactor coupled to a continuous drop tube reactor (DTR) for biomass pyrolysis. Beech wood pyrolysis was initially examined without catalysts at various temperatures (500–600 °C). The products were characterised using GC-MS, Karl Fischer titration, GC-FID/TCD, and thermogravimetric analysis. The highest bio-oil yield (58.8 wt.%) was achieved at 500 °C with a 500 mL/min N2 flow rate. Subsequently, ex situ catalytic pyrolysis was performed using an HZSM-5 catalyst in a fixed-bed reactor at a DTR outlet, operating at 425 °C, 450 °C, and 500 °C. The HZSM-5 catalyst exhibited declining deoxygenation efficiency over time, which was evidenced by decreasing conversion rates of chemical families. Principal component analysis was employed to interpret the complex dataset, facilitating a visualisation of the relationships between the experimental conditions and product compositions. This study highlights the challenges of continuous operation as experimental durations were limited to 120 min due to clogging issues. This research contributes to understanding continuous biomass pyrolysis coupled with catalytic deoxygenation, providing insights into the reactor configuration, process parameters, and catalyst performance crucial for developing efficient and sustainable biofuel production processes.